Creativity from Robert Sternberg’s Perspective - Nađ, Ivona J. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper aims to present and analyze both theories and models of Robert Sternberg, one of the most prolific and well-cited researchers in the field of creativity. A review of his theoretical assumptions reveals a clear shift in his understanding of creativity over time. The first model focuses exclusively on explaining the intrinsic characteristics of the creative individual, while subsequent studies recognize the significance of taking social context into account. In addition to theories that include traits of the creative individual, Sternberg also postulated a model that aims to explain the stages of the creative process. Given the qualitative differences between these two sets of explanations, the text is divided into two sections. First, the fundamental components and logic of each model are briefly presented. Second, models are contrasted with alternative ones that claim to explain the same aspects of creativity. The paper concludes that Sternberg’s theories make a specific contribution to our understanding of creativity. On the other hand, certain contradictions and criticisms are also discussed, along with a potential solution.